Blowfish Algorithm-Securing the Future - Kumari, U.V. Ratna; Pokhrel, Santosh; Anche, Hyndavi Anusha (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
Information security has become a major issue in communication systems. Any threat to the information being transferred may cause severe loss to the organization. To overcome this security threat cryptography techniques are used to encrypt and decrypt the data. Many algorithms are used for this purpose, one among them is the blowfish algorithm. This paper presents a detail regarding theencryption and decryption using blowfish algorithm using VHDL coding and its post simulation results. The beauty of this algorithm lies in its prepossessing way of generating the sub-keys.